Translation Strategies of Javanese Addresses Terms into Arabic in Gadis Kretek Novel - Muhamad Saiful Mukminin; Sajarwa (Suar Betang, 2025)
The differences in address systems between Javanese and Arabic cultures require translation strategies to achieve equivalence. The address systems in these two cultures not only reflect personal relationships, but also distinct social structures and cultural values. This study aims to examine the translation strategies of address terms in the novel Gadis Kretek into Arabic. The method used is descriptive qualitative with a comparative and interpretative approach. The data consists of linguistic units in the form of address terms that represent social relations, closeness, and hierarchy among characters. Data were collected through close reading, identification of address terms in both the source and target texts, recording of data pairs, and transliteration of Arabic text into Latin script. The analytical techniques involved grouping the data, comparing forms and meanings, and identifying translation strategies. The results of the study reveal five translation strategies: borrowing, omission of address terms, contextual paraphrasing, alternative paraphrasing, and cultural substitution. The choice of strategies was influenced by the intention to preserve the source culture, clarity of the target text, lack of direct equivalence, and the context of character relationships. This study asserts that the translation of address terms reflects a complex cross-cultural meaning transfer process, which is not only linguistic, but also social and cultural in nature.